Investigating the Impact of Non-Structural Proteins of Coronaviruses (CoVs), MERS-CoV & SARS-CoV-1, upon the antiviral Interferon-α JAK/STAT Pathway - Zhang, Yamei (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2024)
The recent emergence of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV- 2) highlights the need for greater understanding of the immune evasion mechanisms used by CoVs to subvert antiviral responses. CoVs have had several global outbreaks with relatively high mortality rates, including Middle East Respiratory Syndrome Coronavirus (MERS-CoV), and SARS-CoV-1, which emerged in 2012 and 2002, respectively. Interferon (IFN)-α is the body’s natural antiviral agent, but its Janus kinase/signal transducer and activators of transcription (JAK/STAT) signalling pathway is often antagonized by viruses, thereby preventing the upregulation of essential IFN stimulated genes (ISGs). Therapeutic IFN-α has disappointingly weak clinical responses in MERS-CoV and SARS-CoV-1 infected patients, indicating that these CoVs inhibit the IFN-α JAK/STAT pathway. The non- structural proteins (nsps) of other CoVs have been shown to block IFN responses. Specifically, within SARS-CoV-2, both nsp5 and nsp14 have been shown to block IFN responses, while nsp2 has been documented to reduce ISRE promoter activity. However, the role of nsp2 and nsp5 from MERS-CoV and nsp14 from SARS-CoV-1 upon IFN responses of human epithelial respiratory cells is poorly understood. Therefore, in this study, we investigated the impact of MERS-CoV-nsp2, MERS-CoV-nsp5 and SARS-CoV-1-nsp14 on the IFN-α JAK/STAT pathway in lung alveolar A549 and bronchial BEAS 2b epithelial cells. Our findings indicate that MERS-CoV-nsp2 and SARS- CoV-1-nsp14 increase basal levels of STAT1 and STAT2 in both cell types, while reducing IFN-α-mediated phosphorylation of STAT1-3 and induction of antiviral ISGs. Meanwhile, we observed a basal phosphorylation of STAT1 and STAT2 in A549 cells expressing MERS- CoV-nsp2 and SARS-CoV-1-nsp14. Interestingly, even though IFN-α-mediated induction of pSTAT1-3 was not affected by MERS-CoV-nsp5 expression in BEAS 2b cells, downstream ISG induction was reduced, revealing that MERS-CoV-nsp5 may use a distinct mechanism of suppressing IFN responses. Additionally, all these three viral proteins inhibit STAT1 and STAT2 nuclear translocation, thus dampening IFN-α JAK/STAT pathway. We further explored the factors influencing basal STAT1 and STAT2 phosphorylation and discovered that the expression of MERS-CoV-nsp2 and SARS-CoV-1-nsp14, but not MERS-CoV-nsp5, upregulated IFN-λ1/3, IL-6, and CCL5 in A549 cells. Through using IFN-λ1/3 neutralizing xiv antibodies, we elucidated that the basal phosphorylation of STAT1 and STAT2 was due to induction of IFN-λ1/3 by MERS-CoV-nsp2 and SARS-CoV-1-nsp14 in A549 cells. Furthermore, both MERS-CoV-nsp2 and SARS-CoV-1-nsp14 induced the expression of USP18, a negative regulator of the IFN-α JAK/STAT pathway. The IFN-α unresponsiveness mediated by USP18 was subsequently validated through siRNA knockdown, where we found that silencing of USP18 reinstated IFN-α-mediated STAT1 phosphorylation and ISG induction. In addition to examining the inhibition of IFN-α JAK/STAT signalling by MERS-CoV-nsp5, we explored its potential impact on IFN induction in human epithelial BEAS 2b cells. Our findings revealed that MERS-CoV-nsp5 inhibited TLR3/ High Molecular Weight of poly(I:C) (HMW-poly(I:C))-mediated IFN-β promoter activation and cytokine production. Moreover, MERS-CoV-nsp5 suppressed IFN-β promoter activation triggered by overexpression of key components in the RIG-I-like receptor (RLR) pathway, including RIG-I, MAVS, IKK-ε and IRF3. Notably, MERS-CoV-nsp5 did not impair the expression or phosphorylation of IRF3, but specifically suppressed its nuclear translocation. Further investigation unveiled a direct interaction between MERS-CoV-nsp5 and IRF3. Importantly, the expression of IFN- β was restored after administration of 3C like protease inhibitors targeting nsp5, indicating the suppression of IFN-β production was dependent on the enzymatic activity of nsp5. In conclusion, this study underscores cell line-specific variations in the immune evasion tactics employed by MERS-CoV and SARS-CoV-1 non-structural proteins. These findings shed light on the diverse strategies employed by these CoVs to evade type I IFN antiviral responses, possibly providing evidence for the ineffectiveness of exogenous IFN-α treatment during CoV infection and contributing to our understanding of viral pathogenesis. Therefore, it may be beneficial for future studies to focus on restoring IFN- α responsiveness, as a therapeutic approach to existing and future CoV infections.
APPROVED